2004
DOI: 10.1002/pssb.200304176
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering study on hybrid structures of Zn1−xyCdxMnySe quantum wells with ferromagnetic Co wires

Abstract: Sub-micron scale hybrid structures of Zn 1-x-y Cd x Mn y Se diluted magnetic semiconductor (DMS) quantum wells (QWs) with ferromagnetic Co wires have been fabricated for the purpose of applying local magnetic fields to the DMS-QW. The wire of DMS-QW with the width down to 100 nm was sandwiched between the Co wires. The magneto-optical properties are studied by spin-flip light scattering of paramagnetic Mnions in the DMS. The application of uniform magnetic fields higher than 0.25 T has been attained from the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Since last decade, there has been increased interest in ZnSe because this is a promising candidate for polymer nanocomposite semiconducting devices [5]. The ZnSe is used as cap and buffer layer in hybrid structure of magneto optical devices [6]. The rapid thermal annealing studies carried out by Singh et al [7] and suggested that variation of optical band gap within the range of ZnSe material, which may be due to compositional variation at interface of bilayer and increasing grain size of film with annealing time and R.B.S confirm the mixing of bilayer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since last decade, there has been increased interest in ZnSe because this is a promising candidate for polymer nanocomposite semiconducting devices [5]. The ZnSe is used as cap and buffer layer in hybrid structure of magneto optical devices [6]. The rapid thermal annealing studies carried out by Singh et al [7] and suggested that variation of optical band gap within the range of ZnSe material, which may be due to compositional variation at interface of bilayer and increasing grain size of film with annealing time and R.B.S confirm the mixing of bilayer [7].…”
Section: Introductionmentioning
confidence: 99%